Development of novel additive manufactured hybrid architected materials and investigation of their mechanical behavior. (January 2023) - Kladovasilakis, Nikolaos; Tsongas, Konstantinos; Tzetzis, Dimitrios
Abstract: In the last decade, topology optimization methods have been investigated by a plethora of studies, utilizing architected materials. Furthermore, combining the ability of additive manufacturing (AM) to produce parts with high geometric complexity, lattices, and architected materials have been applied in fully functional AM parts in various applications, such as in biomechanical and aeronautic industries. Also, it is commonly known that lattices lead to severe degradation of the mechanical properties depending on the applied relative density. This study aims to develop novel hybrid architected materials that tend to reduce the degradation of mechanical properties. More specifically, in this paper, strut-lattices and triply periodic minimal surface (TPMS) geometries were combined, depending on their individual mechanical response, in order to create innovative hybrid architected materials with enhanced mechanical properties. Four distinct hybrid cellular materials were developed and fabricated in the current research utilizing advanced design software and Selective Laser Sintering (SLS) AM technique with Polyamide 12 (PA12) as a construction material. The anisotropy of each cellular design through the surface of normalized elastic modulus diagrams and the influence of the selected structures' thickness on the relative density were examined. The mechanical performance of the manufactured representative volume elements of each cellular material was extracted via quasi-static uniaxial compression experiments. Moreover, utilizing the experimental data, hyper-elastic finite element (FE) models were built for each architected material. In addition, specimens with more unit cells were fabricated in order to evaluate the mechanical response of hybrid architected material in a complex structure and validate the developed FE models. To summarize, the developed hybrid architected materials revealed superior mechanical response in comparison with their origin cellular materials, with the SD&FCC structure performing almost double mechanical strength than the Schwarz Diamond structure. Highlights: Mechanical behavior of Hybrid 3D printed Architected Materials. Strut-Lattices, Triply Periodic Minimal Surfaces. Finite element analysis of structures. Selective Laser Sintering 3D printing technique.